2003
DOI: 10.1046/j.1540-8167.2003.03124.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Injection Induces Cardiac Nerve Sprouting and Increased Tenascin Expression in a Swine Model of Myocardial Infarction

Abstract: MSC injected with BM into swine infarct results in overexpression of cardiac tenascin, increased the magnitude of cardiac nerve sprouting in both atria and ventricles, and increased the magnitude of atrial sympathetic hyperinnervation 2 months after injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(100 citation statements)
references
References 31 publications
3
96
1
Order By: Relevance
“…Thus, the expression of SCX and TNC is considered as the marker of tenogenic differentiation in vitro (Schweitzer et al 2001;Hsia 2005; Chiquet-Ehrismann and Tucker 2004). Though, it was illuminated later that in some fibroblasts these two genes were slightly expressed, the expression level in tenocytes was much higher (Pak et al 2003;Seo et al 2004). On the other hand, Collagen types I, III, V, IX, X, XI, XII and XIV are known or thought to be involved in bone, tendon or ligament healing, especially Col I and Col III are the main collagens found in connective tissues, such as tendon and ligament.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the expression of SCX and TNC is considered as the marker of tenogenic differentiation in vitro (Schweitzer et al 2001;Hsia 2005; Chiquet-Ehrismann and Tucker 2004). Though, it was illuminated later that in some fibroblasts these two genes were slightly expressed, the expression level in tenocytes was much higher (Pak et al 2003;Seo et al 2004). On the other hand, Collagen types I, III, V, IX, X, XI, XII and XIV are known or thought to be involved in bone, tendon or ligament healing, especially Col I and Col III are the main collagens found in connective tissues, such as tendon and ligament.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, significantly higher episodes of ventricular fibrillation, both spontaneous and induced, occurred in the hypercholesterolemic rabbits, indicating a lower vulnerability to fibrillation. 49 Cardiac nerve sprouting appears to be highly plastic and has been has been shown in other models of heart failure including rapid pacing where dogs with the most hyperinnervation have the highest risk of sudden cardiac death, 50 in stem cell transplantation, 51 and radiofrequency ablation. 52 Heart failure is also known to cause spatially heterogenous remodeling of cardiomyocytes, with further remodeling of cardiac ion channels, including Ca, K, Cl, and Ca transporters and enzymes in the border zones surrounding the infarct.…”
Section: Myocardial Infarction Heart Failure and Sympathetic Innervmentioning
confidence: 97%
“…Numerous studies with a variety of animal models have shown that MSCs may be useful in the process of repairation or regeneration of damaged bones, cartilages, or myocardial tissues, thus representing a new source to treat congenital or degenerative disorders (Muguruma et al 2003;Pak et al 2003;Parsons et al 2004).…”
Section: Introductionmentioning
confidence: 99%